Analisis Kebutuhan E-Modul Minyak Esensial Serai (Cymbopogon citratus) sebagai Bahan Sediaan Aromaterapik Kosmetik pada Mata Kuliah Workshop Aromatherapy: Systematic Literature Review - Hidayah, Nurul; Armandari, Mari Okatini; Ambarwati, Neneng Siti Silfi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The Aromatherapy Workshop course requires interactive learning media to improve students' practical skills. E-modules can be a solution to teach the use of lemongrass essential oil (Cymbopogon citratus) in making aromatherapy cosmetics. This study aims to analyze the need for the development of an effective lemongrass essential oil-based e-module in vocational beauty education. The method used is Systematic Literature Review (SLR) by collecting and analyzing relevant literature. The results of the study indicate that the use of e-modules can improve students' understanding and skills in practicing the use of lemongrass essential oil, as well as provide insight into the quality indicators of e-modules in learning. The development of lemongrass essential oil e-modules can be a solution to support more effective and contextual learning.